2003
DOI: 10.1108/00251740310509562
|View full text |Cite
|
Sign up to set email alerts
|

Explaining executive integrity: governance, charisma, personality and agency

Abstract: Ethics is a highly controversial topic. It is therefore no surprise that reviewers of papers on this topic are likely to take a different view than that of the authors. After careful consideration, it was decided to include the reviewer's comments as well as replies from the authors and a final word from the reviewer in the Appendix. It was felt that this addition to the paper brings to readers a richer exploration of the topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
2
12
0
1
Order By: Relevance
“…These statements had 6 votes or more to meet the 60% consensus threshold in Round 3. This lends support to the assertions of Tourigny et al (2003) that the lack of exhibited behavior reflecting principles of governance and ethical standards can ca bank failures. Noreen et al (2016) concluded that regulatory authorities must work on the ways to control the moral hazard behavior of banks.…”
Section: Statements That Satisfied the Consensus Thresholdsupporting
confidence: 68%
“…These statements had 6 votes or more to meet the 60% consensus threshold in Round 3. This lends support to the assertions of Tourigny et al (2003) that the lack of exhibited behavior reflecting principles of governance and ethical standards can ca bank failures. Noreen et al (2016) concluded that regulatory authorities must work on the ways to control the moral hazard behavior of banks.…”
Section: Statements That Satisfied the Consensus Thresholdsupporting
confidence: 68%
“…Specifically, leaders' dysfunctional behaviors may be strongly influenced by and enabled by potentially dysfunctional behaviors on the part of followers (see also Clements & Washbush, 1999;Tourigny, Dougan, Washbush, & Clements, 2003). From an ethical standpoint, the charismatic leader who can use imagery to enhance his or her mystical status and engage in impression management tactics can shift attention away from controversial ethical issues toward more socially desirable ends (such as profitability).…”
Section: The Role Of Follower Perceptions and Motivations In Interprementioning
confidence: 97%
“…Therefore, the context of corporate governance, affected both by the internal power and discretion of the CEO and the effects of signals from outside the firm (Firth et al, 2007;Tourigny et al, 2003), is the key factor determining the degree of diffusion of CEO reputation among his TMT, the residual beneficiary of this recognition. Literature has already shown that governance effectiveness significantly differs between countries, and especially between Anglo-Saxon ones such as the UK and USA and those of Continental Europe, among them Spain (Claessens and Yurtoglu, 2013;Balkin, 2008; 541 CEO reputation and TMT compensation La Porta et al, 1999).…”
Section: Introductionmentioning
confidence: 99%